Personalised dietary interventions: a successful approach to chronic GERD management - Sohani, Sikandar; Jooma, Nick; Fatima, Mehak; Taha, Faheem (Journal of the Pakistan Medical Association, 2026)
This case report highlights effective management of chronic Gastroesophageal Reflux Disease (GERD) through a personalised strategy utilising Food Allergy and Sensitivity Testing (FAST) at Infinite Wellness. The patient, burdened with persistent GERD symptoms despite conventional treatment, underwent FAST to identify specific dietary triggers contributing to his condition. Personalised modifications were implemented under the guidance of a dietitian. Within weeks, the patient experienced significant symptom relief, highlighting the efficacy of personalised diet plans. Retesting after six months showed sustained improvement in severity of symptoms and test results, indicating durability of dietary interventions. This case illustrates potential benefits of customised dietary strategies for comprehensive management of GERD. By addressing individual dietary triggers identified through FAST, clinicians can offer patients a targetted approach that complements or reduces reliance on pharmacological treatments. Such interventions improve symptom control and enhance patient’s satisfaction and quality of life by addressing the root causes of GERD systematically. Keywords: Gastroesophageal Reflux Disease, Food, Sensitivity, Diet.